Boosting the entrepreneurial scene in cities: experiences and reflections from the InFocus network - a short communication. (19th July 2019) - Winden, Willem Van
This short communication contains a reflection on local entrepreneurial ecosystems and how to boost them, in the context of smart specialisation strategies of cities and regions. It is based on a literature study and inputs from ten member cities of the InFocus project (sponsored by the EU's URBACT programme), that exchange and develop knowledge about the development of smart specialisation strategies on the urban level. In September 2017, the network held a meeting in Turin, dedicated to the topic of promoting entrepreneurship ecosystems. The paper discusses several specific aspects of policies regarding entrepreneurship: the relation with smart specialisation approach, start-up promotion policies, fostering a culture of entrepreneurship, and the different development stages in entrepreneurship: Starting, scaling, and growing, with examples from cities in the InFocus network. Among other things, it concludes that a stronger alignment between the urban and regional policy levels is required to link the urban-focused start-up ecosystems to the regional industrial tissue.